Cognitive function and quality of life of stroke survivors: A crosssectional study/ Anis Arsyida Abd Rashidd ... [et al.] - Abd Rashidd, Anis Arsyida; Che Daud, Ahmad Zamir; Ab Rahim Yang, Mohd Khairul Anuar; Talib, Siti Salwa (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Stroke is a neurological deficit due to an acute focal injury of the Central Nervous System (CNS) by a vascular cause. It is a major cause of disability and death worldwide. Stroke survivors have to face difficulties in life due to physical disabilities, cognitive impairments and the risk of emotional disturbances that also lead to a reduction of quality of life. Multiple studies have suggested that cognitive decline influences the reduction of quality of life among stroke survivors. There is a limited study on the magnitude of relationship between cognitive functions and quality of life among stroke survivors in Malaysia. Thus, this study aimed to determine relationship of cognitive functions and quality of life of stroke survivors. A cross-sectional study was conducted in three different branches of the National Stroke Association of Malaysia (NASAM) involving 55 individuals who were diagnosed with stroke. To evaluate the cognitive functions and quality of life of the survivors, the St Louis University Mental Exam (SLUMS) and Short version Stroke Specific Quality of Life (SS-QOL) were used. A good positive correlation was observed between SLUMS with SS-QOL psychosocial domain. There was no significant difference in sociodemographic characteristics with cognitive functions and quality of life. The finding suggested that cognitive functions play a role in perceived quality of life as there was a positive correlation between SLUMS and SS-QOL physical domain.